Distribuição espacial das guildas tróficas de peixes estuarinos no litoral amazônico brasileiro - ALMEIDA, Regiane da Silva (2018)
This study was conducted to understand the spatial distribution of fish species on Golfão Maranhense and identify which factors may influence their distribution. It was defined three sampling sites for every 13 studied estuaries. Each site was determined by its location and type of environment. Fish were captured using trawl net with otter boards displaying six meters length by three meters height, with net mesh size of one centimeter between knots. Fish species were classified into trophic guilds after stomach content analyses. It was analyzed 10 stomachs per species for each estuary. It was identified 21 feeding items explored by fish and also the occurrence of some “key feeding items”, suggesting the permanence of some species as function of the abundance of these items. The use of such resources classified fish groups into eight trophic guilds. From the total of 66 species, 14 were placed into more than one trophic guild, exhibiting feeding plasticity. The trophic structure configuration on estuaries from Golfão illustrates some aspects of habitat use by those fish species. Environmental factors such as Organic Matter, Suspended Particulate Matter and pH were mostly associated to Planktivorous, Carnivorous and Larvae-feeding guilds. Whereas factors like Chlorophyll, Conductivity, Dissolved Oxygen, Nitrite, Phaeopigment and Total Dissolved Solids were correlated to the distribution of Detritivores, Piscivorous and Omnivorous guilds. Therefore, we conclude trophic guilds spatial distribution is associated by three factors: environmental conditions; feeding resources availability; and habitat use.